Olive Leaf Extracts as a Source of Antibacterial Compounds against Campylobacter spp. Strains Isolated from the Chicken Food Chain - Jose Manuel Silvan; Rodrigo Casado; Marisol Villalva; Soledad Diaz; Alba Gutierrez-Docio; Esperanza Guerrero-Hurtado; Marin Prodanov; Adolfo J. Martinez-Rodriguez (Biology and Life Sciences Forum, 2021)
Campylobacter is the leading cause of bacterial foodborne gastroenteritis worldwide. Infections by Campylobacter in humans are generally caused by consuming contaminated foods of animal origin, with poultry, especially chicken, being the main reservoir. The high prevalence of Campylobacter in chicken carcasses and the growing resistance to the most widely used antibiotics has driven EFSA to propose a regulation (2017/1495) containing new microbiological criteria to regulate the presence of Campylobacter in broiler carcasses. In this context, there has been an increase in the number of research aimed at the search for new tools to reduce Campylobacter incidence in chicken meat. The objective of the present work was to evaluate the antibacterial activity of two olive leaf extracts (A y B) against eleven Campylobacter spp. strains (C. jejuni y C. coli) isolated from chicken food chain. Results showed that all Campylobacter strains had resistance to at least one of the eight antibiotics evaluated, and 46% of them were antibiotic multi-resistant. HPLC analysis showed that hydroxytyrosol and oleuropein were the major phenolic compounds in extracts A and B, respectively. Extract A showed a significant antibacterial activity against all Campylobacter strains tested in the present work. The use of a pure standard of hydroxytyrosol confirmed the contribution of this compound to the antibacterial effect of extract A. These results suggest that olive leaves could be used as a source of bioactive compounds to obtain extracts with antibacterial activity against Campylobacter spp potentially applicable to reduce the presence of Campylobacter in chicken carcasses.